2017
DOI: 10.1111/php.12753
|View full text |Cite
|
Sign up to set email alerts
|

Proteorhodopsin Photocycle Kinetics Between pH 5 and pH 9

Abstract: The retinal protein proteorhodopsin is a homolog of the well-characterized light-driven proton pump bacteriorhodopsin. Basic mechanisms of proton transport seem to be conserved, but there are noticeable differences in the pH ranges of proton transport. Proton transport and protonation state of a carboxylic acid side chain, the primary proton acceptor, are correlated. In case of proteorhodopsin, the pK of the primary proton acceptor Asp-97 (pK ≈ 7.5) is unexpectedly close to environmental pH (pH ≈ 8). A signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 67 publications
(133 reference statements)
1
11
0
Order By: Relevance
“…Hence, this would indicate that 510 nm light can trigger the photocycle somewhat more efficiently than 620 nm light, implying that the hypsochromic ground-state species is somewhat more dominant in producing a functional photocycle in PR:A2. On the other hand, higher production of the M-intermediate with blue light under acidic conditions was also reported for PR:A1 50 and hence could simply be the result of populating higher energy vibronic states on the excited state surface. For PR:A1, it has been reported that the general scheme of the photocycle is similar at pH 7 and pH 9, be it that the kinetics and quantities of the photoproducts may vary.…”
Section: Results and Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Hence, this would indicate that 510 nm light can trigger the photocycle somewhat more efficiently than 620 nm light, implying that the hypsochromic ground-state species is somewhat more dominant in producing a functional photocycle in PR:A2. On the other hand, higher production of the M-intermediate with blue light under acidic conditions was also reported for PR:A1 50 and hence could simply be the result of populating higher energy vibronic states on the excited state surface. For PR:A1, it has been reported that the general scheme of the photocycle is similar at pH 7 and pH 9, be it that the kinetics and quantities of the photoproducts may vary.…”
Section: Results and Discussionmentioning
confidence: 65%
“…For PR:A1, it was reported that at acidic to neutral pH, the M-like intermediate is formed with components of 2–4 μs and several tens of μs. 49,50 Hence, the dominant M formation in PR:A2 (67 μs) seems to be somewhat slower than in PR:A1, while the minor M formation proceeds at almost the same rate in both pigments.…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The protonation state of our model corresponds to an alkaline environment, hence we take an experimental absorption maximum at 2.40 eV (516 nm) that was determined at pH 9.2. 9 An experimental absorption maximum cannot be compared directly to a vertical excitation energy, hence we are not expecting to have a one to one correspondence with the computed values. Nevertheless, we observe that all methods are yielding excitation energies within a range of 0.25 eV.…”
Section: Geometry Optimization and Excitation Energiesmentioning
confidence: 95%
“…The deprotonation of D97 leads to a spectral shift from 544 nm at pH 5 to 516 nm at pH 9. 9 This effect of the electrostatic environment on the wavelength or colour of the absorbed light by the chromophore can be explained by the point charge model. 10 Briefly, the chromophore absorption is fine-tuned by the protein surrounding, in particular by the immediate environment in the so-called protein binding pocket.…”
Section: Introductionmentioning
confidence: 99%